Avaliação do atributo da integralidade na atenção primária à saúde em municípios da região centro-oeste no Rio Grande do Sul: PCATool-Brasil versão profissionais - Pucci, Vanessa Rodrigues (2017)
Primary Health Care is defined as the first level of care within the health system, characterized by the continuity and integrality of care, coordination of care, family-centered attention, community orientation and participation, and the cultural competence of professionals. Thus, its four essential attributes, among which, the attribute of completeness, are defined. In this context, the evaluation becomes essential, since it makes possible the knowledge about the effectiveness of the health care system, corroborating with improvements in the processes in search of better results. Thus, the objective of this study is to evaluate the integrality of health in Primary Health Care services in the municipalities that make up the 4th Regional Health Coordination of Rio Grande do Sul, which includes the Health Regions Verdes Campos and Entre Rios. This is a study with a quantitative, transversal approach, integral to the matrix design "PCATool (Primary Care Assessment Tool) Assessment of Primary Care in the 4th Regional Health Coordination of the State of Rio Grande do Sul. Data collection occurred between months of February and July of 2015, carried out in a computerized way with the use of the instrument Primary Care Assessment Tool - Brazil professional version, as well as through a socio-demographic questionnaire. The evaluated attribute is subdivided into two components: Available Services and Rendered Services. The analysis was performed using Statiscal Analisys System version 9.0. The score obtained was dichotomized at a low score <6.6 and a high score ≥6.6. The Shapiro Wilk test was used to distribute the variables normality. Pearsson's correlation was used to verify the degree of dependence between the items of both components, and their scores, and the Poisson regression to identify association between the score and its socio-spatial context. The ethical precepts respected Resolution 466/2012. The sample consisted of 207 higher-level health professionals, mostly female, self-declared whites, nurses, with a mean age of 39.2 years. Regarding to the results of this study: in the first article, it was observed that both components obtained a higher score than the point of classification necessary to configure the presence and extent of integrality in health services, in the second article, a multilevel study in two levels (contextual and individual), the prevalence of the attribute of completeness associated with the population size of the municipalities evaluated was obtained, in the third article, through an integrative review, was verified that home care can influence the effectiveness of primary care, in the fourth article, a narrative review showed a low scientific production regarding the integrality in Primary Health Care, where the greatest tendency found concerns to the health care practices of the elderly. It was possible to verify that health professionals are contributing to the principle of integrality in the health services. It is expected that this study can contribute to the achievement of this principle, so that actions performed in this scenario be able to understand the person within its context, social, family and biological.